2013
DOI: 10.1530/erc-13-0150
|View full text |Cite
|
Sign up to set email alerts
|

Morphofunctional effects of mitotane on mitochondria in human adrenocortical cancer cells

Abstract: At present, mitotane (MTT) represents the first-line pharmacological approach for the treatment of advanced adrenocortical carcinoma (ACC). Despite clear evidence that the drug can reduce the clinical signs of steroid excess in secreting ACC, the mechanism mediating the possible toxic effect of MTT on tumor cells still remains obscure. This study investigated the intracellular events underlying the toxic effect of MTT by studying qualitative and quantitative alterations in mitochondrial morphology and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 28 publications
(37 reference statements)
6
43
0
4
Order By: Relevance
“…This was confirmed to some extent in cell culture suggesting that down-regulation of the mitochondrial respiratory chain might be involved in the cytotoxic effect of the drug (37,38). We personally have some doubts if the covalent binding of a mitotane intermediate to mitochondrial proteins is actually causative of decreased steroid synthesis and cell death in ACCs as i) in the original report, protein adducts have been mainly found in non-human adrenocortical tissue and only weakly in NCI-H295 cells, ii) these presumed adducts have never been identified, and iii) alterations of the respiratory chain also occur during apoptosis which may be triggered by completely separate pathways.…”
Section: Mitotanementioning
confidence: 63%
“…This was confirmed to some extent in cell culture suggesting that down-regulation of the mitochondrial respiratory chain might be involved in the cytotoxic effect of the drug (37,38). We personally have some doubts if the covalent binding of a mitotane intermediate to mitochondrial proteins is actually causative of decreased steroid synthesis and cell death in ACCs as i) in the original report, protein adducts have been mainly found in non-human adrenocortical tissue and only weakly in NCI-H295 cells, ii) these presumed adducts have never been identified, and iii) alterations of the respiratory chain also occur during apoptosis which may be triggered by completely separate pathways.…”
Section: Mitotanementioning
confidence: 63%
“…Many inhibitors of electron transport as well as of F1F0-ATPase cause cell death under conditions that require respiration, but not under glycolytic conditions (Marroquin et al 2007; Poli, et al 2013; Tettamanti, et al 2008). Numerous inhibitors of oxidative phosphorylation have been investigated as potential anti-cancer agents (Rohlena, et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Besides VDAC2, we also detected VDAC1 in the human epithelial thyroid tumours and in the thyroid cell lines. In 2010, Koren et al showed that this isoform is essential for normal growth of tumoural cells, and that silencing VDAC1 expression in T-Rex-293 cells by means of RNA interference reduced ATP production and decreased cell growth (Koren et al, 2010).…”
Section: Discussionmentioning
confidence: 99%